Talent Acquisition Strategies: A Comprehensive Examination of Recruitment Policies for Organizational Success - Opada, Fany Marice Mince; Ibrahim, Muhdi B. Hi; Irawan, Andri; Akbar, Muhammad Aldrin; Rasyid, Abdul (Advances in Human Resource Management Research, 2024)
This research aims to investigate talent acquisition strategies employed by organizations across diverse industries and sectors, focusing on their alignment with organizational objectives, legal requirements, and diversity initiatives. The study employs a qualitative research approach, utilizing a comprehensive review of existing literature and case studies to analyze various talent acquisition strategies and their implications. Findings reveal a spectrum of proactive and reactive strategies, including talent pipelining, employer branding, succession planning, job postings, referrals, and engagement with recruitment agencies. Moreover, the integration of technology, particularly artificial intelligence (AI) and data analytics, has revolutionized talent acquisition practices, offering opportunities for efficiency and candidate engagement. However, the adoption of technology-driven solutions also presents challenges related to data privacy, algorithmic bias, and transparency. Ethical considerations surrounding the responsible and equitable use of technology in recruitment are discussed, emphasizing the importance of proactive measures to mitigate biases and ensure fairness. Overall, this research underscores the strategic importance of aligning talent acquisition strategies with organizational objectives and diversity initiatives to drive organizational success and competitiveness.